Effect of Ilex x meserveae Aqueous Extract on the Quality of Dry-Aged Beef - Anna Marietta Salejda; Aleksandra Szmaja; Łukasz Bobak; Anna Zwyrzykowska-Wodzińska; Anna Fudali; Przemysław Bąbelewski; Maciej Bienkiewicz; Grażyna Krasnowska (Journal of Food Quality)
The effect of meat marinating with aqueous extract of Ilex meserveae dried leaves on dry-aged beef quality was investigated. Shear force, TBARS value, color parameters, fatty acid profile, and sensory properties were evaluated in beef cuts dry-aged for 21 days. The use of Ilex meserveae dried leaves as marinade at 0.5, 1.0, and 2.0% w/v did not affect the shear force and color parameters of dry-aged beef. The marinating of beef cuts with Ilex meserveae resulted in efficient prevention of lipid oxidation without impairing sensory acceptability. Aqueous extract Ilex meserveae can be applied as a natural ingredient in meat marinade to prevent peroxidation.